Potensi Simpanan Karbon Vegetasi Penyusun Hutan Kota di Kecamatan Pare, Kabupaten Kediri - John Bosco Da Costa; Rawana; Tatik Suhartati (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2026)
Rapid urban development has led to increased carbon dioxide (CO2) emissions and a decline in environmental quality. Urban forests serve as an ecological solution through the ability of vegetation to sequester and store carbon. This study was conducted at Ringin Budho Urban Park and Kilisuci Urban Park in Pare District, Kediri Regency, with the aim of identifying vegetation composition and calculating carbon stock potential on site. The method employed was a vegetation census using a nested plot approach (20m x 20m), followed by biomass estimation using the allometric equation from Chave et al. (2005) and carbon conversion based on the National Standardization Agency (2019) standards. The results showed that the urban forests in Pare District consist of 17 species from 14 families, with a total of 220 individuals. The carbon stock potential reached 52,406.90 tons Carbon /ha, with the largest contribution coming from the Rain Tree (Samanea saman) at 98.60%. Analysis based on vegetation level revealed a dominance of mature trees, accounting for 98.22% of the carbon stock. Based on wood density categories, the moderately heavy group (0.60 - 0.75) contributed 98.72% of the total carbon stock. A comparison between locations indicated that Kilisuci Urban Park has a higher carbon stock compared to Ringin Budho Urban Park.This research demonstrates that the presence of species with large biomass and high wood density is crucial in determining the carbon storage capacity of urban forests. These findings can serve as a basis for managing urban green open spaces to support climate change mitigation.